Investigation of the presence and seasonal prevalence of Salmonella spp., Salmonella Typhimurium, and its monophasic variant I 4,5,12:i:- in United States swine feed mills - Boccatto, Gabriela Magossi (Kansas State University, 2018)
Salmonella is an important pathogen of public health concern. Each year, Salmonella costs the food industry approximately $2.3 billion. In recent years, the number of cases of Salmonella linked to pork products has also increased in the United States (US). Although pork has the lowest association with human foodborne illness when compared to beef and chicken, it is the most consumed meat in the world. Therefore, Salmonella is a significant food safety concern for the American swine industry. This pathogen can be present along all the food production chain from farm to fork and recent studies reported the isolation of Salmonella enterica serovar Typhimurium (ST) and its monophasic variant 4,[5],12:i:- (STM) in feed and feed ingredients. The occurrence of these pathogens in the pre-harvest environment can translate to entry and contamination of the human food chain. Nevertheless, little is known about Salmonella incidence and association with these types of environments. Hence, the purpose of this study was to investigate the presence and seasonal prevalence of Salmonella spp., ST and STM in selected feed mills, among the major US swine feed production areas. Eleven swine feed mills in eight different states were selected. Six mills produced only mash feed, while the other five facilities produced both mash and pelleted feed. Visits were conducted during fall 2016, early spring 2017 and summer 2017. Twelve environmental samples were collected within each facility and season, representative of the production flow, from receiving of ingredients to the finished product, including floor surfaces, equipment dust, workers’ shoes, and finished feed. Samples were analyzed following the USDA-FSIS guidelines and culture positive samples were analyzed by PCR. A multiplex PCR assay was also performed to differentiate Salmonella Typhimurium and Salmonella I 4,[5],12:i:- from the other serotypes. Associations between mill, season, mill type, sample site and Salmonella prevalence were analyzed using generalized linear mixed models (P < 0.05). From the 383 samples collected, 49 (12.8%) were identified as Salmonella spp.; two (5.1%) were identified from feed, while the other 47 (13.7%) originated from equipment or surfaces. Two samples were positive for ST and three for STM by multiplex PCR. Mill (P = 0.003) and season (P = 0.006) were statistically associated with the presence of Salmonella, with higher prevalence in fall and summer (13.2%) as compared to spring (3.6%). These findings demonstrate the seasonal prevalence of Salmonella spp., ST and STM in feed mills across the US, highlighting the potential role of the feed mill environment as a microbial entry route into the human food chain. The data presented can be also used as a tool to assist in the implementation of mitigation strategies for pre-harvest food safety.
Keywords: Feed mills; Salmonella; Salmonella Typhimurium; Salmonella 4,5,12:i:-; seasonality; entry route